Ukrainian migration to the European Union : lessons from migration studies - Fedyuk, Olena; Kindler, Marta (IMISCOE Research Series, 2016)
This book brings together research findings from a variety of disciplines in this integrated study of the migration of Ukrainian nationals to the EU. It contextualizes and historicizes this migration against the background of the series of crises experienced by Ukraine and the wider region over the last thirty or so years, from the dissolution of the USSR, through EU border changes, to the failed economic reforms of independent Ukraine. The book reviews major publications in a variety of disciplines and in several languages, including Russian, Ukrainian and English. It provides a critical analysis of these authoritative sources, linking historical and contemporary texts to establish a longitudinal perspective on migration trends and practices. The spatial, temporal, gender and geopolitical aspects of migration are examined, with expert analysis of the implications for economics, immigration policies, and migration studies. The contributors also draw on national and international academic research and country-specific data to describe the experience of Ukrainian migration in six European countries: Poland, the Czech Republic, Greece, Italy, Portugal, and Spain. These detailed portraits identify the principal trends and will help researchers, policy makers, and students to a better understanding of the dynamics of migration flow in the region as a whole. "A timely volume covering many cases and many facets of Ukrainian mobility in the EU. A must have for all libraries." Anna Triandafyllidou, Robert Schuman Centre for Advanced Studies (RSCAS) "Is Ukraine the Mexico of Europe, I once asked. It is one of the most eminent migration cases to study. This book fills an acute knowledge gap and is a rich and important contribution." Franck Dvell, University of Oxford "This collection offers a comprehensive historical and geographical analysis of various migratory patterns from Ukraine to different European countries. It is a must read for migration scholars and for anyone interested in this highly topical phenomenon." Lena Nre, University of Helsinki